Assessment of gene action association involved with economic traits of black carrot (Daucus carota) - SELVAKUMAR, RAMAN; MANJUNATHAGOWDA, D C; KALIA, PRITAM; RAJE, R S (The Indian Journal of Agricultural Sciences, 2021)
Carrots (Daucus carota L.) are rich sources of vitamins, phytonutrients, bioactive compounds and health promotingproperties. Recent increased awareness of nutritional security has resulted in a dramatic increase in carrot consumption,necessitating increased carrot production by farmers and growers. Understanding the genetic design of economictraits including root length, root weight, root diameter, core diameter, and flesh thickness, as well as developing anappropriate breeding plan for these traits, will help accomplish those ambitious goals. Gene action experiments wereconducted at ICAR-Indian Agricultural Research Institute during 2012–15 in order to estimate the type and magnitudeof gene action in order to develop a breeding strategy for recognizing segregants with desirable horticultural traits.Four inbred lines such as Pusa Asita, Pusa Rudhira, Pusa Kulfi, Pusa Meghali were used to develop three crosses, viz.Pusa Asita × Pusa Kulfi, Pusa Asita × Pusa Meghali, Pusa Asita × Pusa Rudhira to achieve the objectives. The findingsconfirmed that the exact composition of gene effects varied through crosses and demonstrated the role of additiveas well as non-additive gene effects in the inheritance of different traits, with a preponderance of the latter. Due tothe parallel function of complementary gene effects, non-epistatic gene interactions for economic yield contributingtraits have been found; thus, hybrid exploitation could be efficiently used by heterosis breeding by using favourablepositive [h] and [l] gene interaction and effects. This genetic information is more helpful to formulate suitable breedingmethodology for identifying the segregants with desirable horticultural traits.